Politicized disease surveillance: A theoretical lens for understanding sociopolitical influence on the monitoring of disease epidemics. (December 2021) - Fisher, Michael P.
Abstract: Sociopolitical forces commonly influence the collection, analysis, dissemination, and general perceptions of epidemiological information. Yet few theoretical lenses provide insight into the mechanisms through which such influence occurs. In this article, I draw and expand upon empirical findings to propose a novel theoretical lens, politicized disease surveillance, which I define as extreme or undue sociopolitical influence on public health surveillance systems or processes in ways that impact disease incidences and prevalences, or estimates or perceptions thereof. This lens foregrounds disease incidence and prevalence as objects of contestation and policy influence and articulates how certain facets of sociopolitical forces shape disease incidences and prevalences—especially amid an epidemic—through one or more channels: (1) the diagnostic construct; (2) screening tools, procedures, or systems; or (3) the behaviors of individuals who are living with or at risk for a certain disease. I provide several contemporary illustrations of politicized disease surveillance and discuss its theoretical and practical implications. Highlights: Sociopolitical forces influence epidemiological systems and disease realities. This article proposes a novel theoretical lens, politicized disease surveillance . The theory examines extreme or undue sociopolitical influence on public health. It analyzes various types of sociopolitical impact and channels and tools used.